Reverese Engineering Burnishing Tool Untuk Proses Finishing Kekasaran Permukaan Pada Mesin Milling Konvensional - Thopo Antonius Adi Soetopo; Mohammad Yazid Diratama; Andri Suhendri .; Ahmad Fauzi . (TURBO [Tulisan Riset Berbasis Online], 2025)
The advancement of the manufacturing industry demands improved surface quality for components produced by conventional milling processes. Typically, grinding is required to achieve surface roughness levels up to N4; however, this process involves significant machine investment and high operational costs. This study presents the design of a burnishing tool as a finishing aid that can be mounted directly onto a conventional milling machine spindle without the need for additional equipment. The tool was developed using the systematic design methodology VDI 2222 and a manufacturing plan involving turning, milling, and grinding of the tool components. Test specimens made of ST37 and S45C steel were initially milled to a surface roughness (Ra) of 2.6–5.7 µm, then burnished using a feed depth of 0.5 mm and spring deflection ranging from 0 to 1.5 mm. The experimental results showed a significant reduction in Ra, reaching as low as 0.16 µm for ST37 and 0.17 µm for S45C. These findings demonstrate the effectiveness of the burnishing tool in enhancing surface finish efficiently and economically using conventional milling machines.